2022
DOI: 10.1039/d2qm00133k
|View full text |Cite
|
Sign up to set email alerts
|

A nano-catalyst promoting endogenous NO production to enhance chemotherapy efficacy by vascular normalization

Abstract: Poor perfusion and low accumulation of drugs caused by abnormal tumor blood vessels significantly reduce the chemotherapy efficacy. Nowadays, the synergistic therapy of vascular normalization and chemotherapy has become an...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…We also assessed the pericyte coverage by co-staining the tumor tissue sections with the vessel marker CD31 and pericyte marker α-SMA. As shown in Figure A, the red fluorescence observed in the Cu 2 O@Dex group suggested that pericytes were properly attached to endothelial cells after treatment . Meanwhile, the semi-quantification results demonstrated that the pericyte coverage (α-SMA/CD31) increased to 33.9% after the Cu 2 O@Dex treatment (Figure B).…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…We also assessed the pericyte coverage by co-staining the tumor tissue sections with the vessel marker CD31 and pericyte marker α-SMA. As shown in Figure A, the red fluorescence observed in the Cu 2 O@Dex group suggested that pericytes were properly attached to endothelial cells after treatment . Meanwhile, the semi-quantification results demonstrated that the pericyte coverage (α-SMA/CD31) increased to 33.9% after the Cu 2 O@Dex treatment (Figure B).…”
Section: Resultsmentioning
confidence: 83%
“…As shown in Figure 5A, the red fluorescence observed in the Cu 2 O@Dex group suggested that pericytes were properly attached to endothelial cells after treatment. 21 Meanwhile, the semi-quantification results demonstrated that the pericyte coverage (α-SMA/CD31) increased to 33.9% after the Cu 2 O@ Dex treatment (Figure 5B). The improvement of vessel normalization after Cu 2 O@Dex treatment could be attributed to the sustainable generation of the NO catalyst by the released Cu + .…”
Section: Vasculature Normalization Ability Of Cu 2 O@dex Nps In Vivomentioning
confidence: 93%
See 1 more Smart Citation